Is the efficiency of banks degenerating due to the mounting of non-performing assets? An empirical investigation using DEA - Maity, Sudarshan; Sahu, Tarak Nath (UUM Press, 2019)
Indian banking system is saddled with bad loans which have resulted in huge losses. Profitability remains a concern due to the rise of NPAs. Investors should not expect high reporting profits from banks due to the ascending provision of the NPAs. Banks are not performing well, and they may not be much efficient due to the rise of NPAs daily. Using data envelopment analysis, the present study intends to assess technical efficiency of banks. As the requirement of homogeneity is fulfilled, the input oriented CCR model is applied. The study finds that the number of efficient banks has shortened, and the average overall technical efficiency of selected banks moves downward throughout the study period. It also reveals that the inefficiency is mostly due to the upward trend of NPAs. Asset quality plays the most crucial role toward the performance of banking sector. Thus, banks and regulators should control the upward trend of NPAs to enhance the efficiency level.